2020
DOI: 10.48550/arxiv.2002.05413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dieudonné Theory via Cohomology of Classifying Stacks

Abstract: We prove that if G is a finite flat group scheme or a p-divisible group, then the second crystalline cohomology of its classifying stack H 2 crys (BG) recovers the Dieudonné module of G. We also prove mixed characteristic analogues of this result using prismatic cohomology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Example 2.5.6. In [Mon20] it is shown that for a finite group G over a perfect field k of characteristic p the corresponding Dieudonné module M (G) can be expressed as H 2 crys (BG/k) with the natural Frobenius action on it.…”
Section: Thenmentioning
confidence: 99%
See 1 more Smart Citation
“…Example 2.5.6. In [Mon20] it is shown that for a finite group G over a perfect field k of characteristic p the corresponding Dieudonné module M (G) can be expressed as H 2 crys (BG/k) with the natural Frobenius action on it.…”
Section: Thenmentioning
confidence: 99%
“…At the same time the idea of using classifying stacks to construct examples of schemes with a certain pathological behavior of cohomology (which goes back at least to [Ser58]) has bore some fresh fruit with the construction of counterexamples to degeneration of the HKR spectral sequence in char p and Hodge-de Rham degeneration over ramified mixed characteristic local rings in [ABM19] and [Li20] respectfully. Besides that in [Mon20] the classical notion of a Dieudonné module (as well as the more recent prismatic Dieudonné module of [AB19]) of a p-divisible group was given a natural interpretation in terms of crystalline (resp. prismatic) cohomology of the corresponding classifying stack.…”
Section: Introductionmentioning
confidence: 99%